Alterations in metabolic pathways in gastric epithelial cells infected with Helicobacter pylori. (November 2018) - Matsunaga, Shinsuke; Nishiumi, Shin; Tagawa, Ryoma; Yoshida, Masaru
Abstract: Helicobacter pylori ( H. pylori ), which is a spiral-shaped Gram-negative microaerobic bacterium, is a causative pathogen. The entry of H. pylori into gastric epithelial cells involves various host signal transduction events, and its virulence factors can also cause a variety of biological responses. In this study, AGS human gastric carcinoma cells were infected with CagA-positive H. pylori strain ATCC43504, and then the metabolites in the AGS cells after the 2-, 6- and 12-h infections were analyzed by GC/MS-based metabolomic analysis. Among 67 metabolites detected, 11 metabolites were significantly altered by the H. pylori infection. The metabolite profiles of H. pylori -infected AGS cells were evaluated on the basis of metabolite pathways, and it was found that glycolysis, tricarboxylic acid (TCA) cycle, and amino acid metabolism displayed characteristic changes in the H. pylori -infected AGS cells. At 2 h post-infection, the levels of many metabolites related to TCA cycle and amino acid metabolism were lower in H. pylori -infected AGS cells than in the corresponding uninfected AGS cells. On the contrary, after 6-h and 12-h infections the levels of most of these metabolites were higher in the H. pylori -infected AGS cells than in the corresponding uninfected AGS cells. In addition, it was shown that the H. pylori infection might regulate the pathways related to isocitrate dehydrogenase and asparagine synthetase. These metabolite alterations in gastric epithelial cells might be involved in H. pylori -induced biological responses; thus, our findings are important for understanding H. pylori- related gastric diseases. Highlights: We performed metabolome analysis AGS human gastric carcinoma cells infected with CagA-positive H.pylori strain ATCC43504. We evaluated the H. pylori -induced modulation of glycolysis, TCA cycle, and amino acid metabolism via metabolite profiling. H. pylori infection caused various metabolite alterations in gastric epithelial cells.